1983
DOI: 10.1210/jcem-57-6-1221
|View full text |Cite
|
Sign up to set email alerts
|

Urinaryγ-Carboxyglutamic Acid and Serum Osteocalcin as Bone Markers: Studies in Osteoporosis and Paget’s Disease*

Abstract: Osteocalcin is a major bone matrix protein with high affinity for hydroxyapatite. This property is conferred by several residues of the calcium-binding amino acid gamma-carboxyglutamate (Gla), which requires vitamin K for its biosynthesis. Because this protein may play a role in the local control of calcium deposition or removal in mineralized tissue, we measured circulating osteocalcin levels and urinary excretion of its breakdown product, Gla, in patients with osteoporosis and Paget's disease. Studies were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(42 citation statements)
references
References 16 publications
2
37
0
3
Order By: Relevance
“…It is known as a potent angiogenic stimulus and a strong mitogen for the stimulation of both prostate cancer and osteoblast growth (42). It has been confirmed that basic fibroblast growth factor can induce hOC promoter activity independent of vitamin D 3 and retinoid activation (43). Furthermore, bone growth factors such as bone morphogenetic protein induce the expression of Runx2 in cells where it is not normally expressed (44).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It is known as a potent angiogenic stimulus and a strong mitogen for the stimulation of both prostate cancer and osteoblast growth (42). It has been confirmed that basic fibroblast growth factor can induce hOC promoter activity independent of vitamin D 3 and retinoid activation (43). Furthermore, bone growth factors such as bone morphogenetic protein induce the expression of Runx2 in cells where it is not normally expressed (44).…”
Section: Discussionmentioning
confidence: 97%
“…Upon addition of vitamin D 3 , all the AI prostate cancer cell lines (DU145 and PC3) and MG63 showed an elevated level of hOC mRNA. However, the androgen-dependent/sensitive nontumorigenic prostate cancer cell LNCaP did not have any hOC expression in either the presence or absence of vitamin D 3 .…”
Section: Androgen-independent Metastatic Human Prostate Cancer Cell Lmentioning
confidence: 87%
See 2 more Smart Citations
“…Biochemical markers of bone resorption (C-terminal cross-linking telopeptide of type I collagen [CTx] and N-terminal cross-linking telopeptide of type I collagen [NTx]) increase during the menopause and remain elevated in postmenopausal women until the ninth decade of life. (15) In patients with postmenopausal osteoporosis and vertebral fractures, the mean level of serum osteocalcin has been reported to be either normal (11,15,16) or slightly elevated (17,18) but always with a wide spectrum of individual values. That heterogeneity can explain the differences according to the population studied.…”
mentioning
confidence: 99%